Conservative approach to Hepatic Portal Venous Gas: A case report. (2017) - Ginesu, G.C.; Barmina, M.; Cossu, M.L.; Feo, C.F.; Fancellu, A.; Addis, F.; Porcu, A.
Highlights: Hepatic Portal Venous Gas (HPVG) is a rare condition often associated with a significant underlying pathologies. The mechanism underlying the passage of the gas from the intestine into the mesenteric, then portal, venous system is not fully understood. The high mortality rate made HPVG a cause of mandatory explorative laparotomy throughout the last fifty years of the twentieth century. The frequent presence of benign conditions underlying this condition has diverted the common therapeutic approach to more cautious options. Abstract: Introduction: Hepatic Portal Venous Gas (HPVG), a rare condition in which gas accumulates in the portal venous circulation, is often associated with a significant underlying pathology, such as Crohn's disease, ulcerative colitis, diverticulitis, pancreatitis, sepsis, intra-abdominal abscess, endoscopic procedures, mesenteric ischemia, abdominal trauma. Presentation of case: Here we report a case of HPVG in an 82-year-old patient who underwent a left colectomy for stenosing tumor of the descending colon. The patient was treated conservatively, and his symptoms resolved. Follow-up computed tomography (CT) scan showed complete resolution of HPVG. Discussion: The mechanism underlying the passage of the gas from the intestine into the mesenteric, then portal, venous system is not fully understood. Historically, this condition has been related to acute intestinal ischemia, as a consequence of a bacterial translocation through a wall defect. Conclusion: This case underscores the role of conservative management, highlighting how the severity of the prognosis of HPVG should be related to the underlying pathology, and not influenced by the presence of HPVG itself.